Epidemic Thresholds in SIR and SIIR Models Applying an Algorithmic Method (2008)
ABSTRACT: Epidemic thresholds were deduced and simulated from SIR models of Susceptible – Infected – Recovered individuals, through local stability analysis of the disease free and endemic equilibrium, with an algorithmic method. One and two types of infected individuals were modeled, considering the influence of subclinical, undiagnosed or unrecognized infected cases in disease transmission.